The Impact of Foreign Direct Investment on the Host Economy of FDI: The Case of China – a Review of Research (Economic and Political Thought, 2023)
The aim of this article is to review the research on the impact of FDI on the economy of FDI host country and to identify the main areas of research. The example of China as an FDI host country is of interest because of the importance of FDI in the developmentof its economy in the period from the implementation of the reform and opening-up policy to the present day. China has become the largest recipient of FDI among developing countries and the second largest recipient of FDI in the world after the US. Selected academic publications in the period from 2000 to 2023 on the impact of FDI on the economy of the host country of this investment were analysed. Their review and analysis also allowed for the identification of the main areas of research. Differences in measurement methods, models, the size of the research samples, the time span of the research, the types of countries covered and the resulting generalisations are the main limitations. Nevertheless, this review is valuable, especially for researchers to deepen research on selected areas of the impact of foreign direct investment on the economy of the FDI host country. The conclusions may also help host country authorities to define FDI policies in order to harness the positive or reduce the negative impact of FDI on the host country.
Keywords: foreign direct investment, FDI, capital flows, economy, FDI host economy, China